METTL16 is Required for Meiotic Sex Chromosome Inactivation and DSB Formation and Recombination during Male Meiosis - Lisha Yin; Nan Jiang; Wenjing Xiong; Shiyu Yang; Jin Zhang; Mengneng Xiong; Kuan Liu; Yuting Zhang; Xinxin Xiong; Yiqian Gui; Huihui Gao; Tao Li; et al. (Advanced Science)
Abstract Meiosis in males is a critical process that ensures complete spermatogenesis and genetic diversity. However, the key regulators involved in this process and the underlying molecular mechanisms remain unclear. Here, we report an essential role of the m6A methyltransferase METTL16 in meiotic sex chromosome inactivation (MSCI), double‐strand break (DSB) formation, homologous recombination and SYCP1 deposition during male meiosis. METTL16 depletion results in a significantly upregulated transcriptome on sex chromosomes in pachytene spermatocytes and leads to reduced DSB formation and recombination, and increased SYCP1 depositioin during the first wave of spermatogenesis. Mechanistically, in pachytene spermatocytes, METTL16 interacts with MDC1/SCML2 to coordinate DNA damage response (DDR) and XY body epigenetic modifications that establish and maintain MSCI, and in early meiotic prophase I, METTL16 regulates DSB formation and recombination by regulating protein levels of meiosis‐related genes. Furthermore, multi‐omics analyses reveal that METTL16 interacts with translational factors and controls m6A levels in the RNAs of meiosis‐related genes (e.g., Ubr2) to regulate the expression of critical meiotic regulators. Collectively, this study identified METTL16 as a key regulator of male meiosis and demonstrated that it modulates meiosis by interacting with MSCI‐related factors and regulating m6A levels and translational efficiency (TE) of meiosis‐related genes.